Pengaruh Mutu Manajemen Berbasis Sekolah Dan Revitalisasi Fungsi Kepala Sekolah Terhadap Kompetensi Guru Di Lima Sekolah Dasar Swasta Se-Kota Samarinda - Ika Nur Ini; Laili Komariyah; Sugeng (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
This study aims to determine the effect of the quality of school-based management and the revitalization of the principal's function on teacher competence in five private elementary schools throughout the city of Samarinda. This study uses a survey method with a causal quantitative approach (cause and effect). The population in this study amounted to 149 teachers with a sample of 109 teachers who were determined through a random probability sampling technique in five private primary schools accredited A, namely; SD Islam Aljawahir, SD Islam Fastabiqul Khairat, SD Kristen Sunodia, SD Katholik 3 W.R Soepratman, dan SD Budi Bakti. The data collection technique used a closed questionnaire which had been tested for validity and reliability. Data analysis used descriptive inferential statistics, with simple and multiple linear regression which included partial test (T test), simultaneous test (F test) and calculation of the coefficient of determination (R2). The results showed that; (1) there is a significant influence on the quality of school-based management (X1) of 50.10% on teacher competence (Y), (2) there is a significant effect of revitalizing the function of principals (X2) of 62.00% on teacher competence (Y), and (3) there is a jointly significant effect between the quality of school-based management (X1) and the revitalization of the principal's function (X2) of 64.20% on teacher competence (Y).